Pengaruh Aksesibilitas, Fasilitas Dan Daya Tarik Terhadap Kepuasan Pengunjung Taman Metro Indonesia Indah Kota Metro Lampung - Sari, Resi Novita; Riyanto, Kuncoro Budi (Universitas Muhammadiyah Metro, 2023)
This study aimed to determine the effect of accessibility, facilities, and attractiveness on visitor satisfaction of Taman Metro Indonesia Indah, Metro City, Lampung. This research was conducted on visitors to Taman Metro Indonesia Indah, Metro City, Lampung, in 2021. This type of research used qualitative and quantitative research. Data collection was obtained by distributing questionnaires in questions about accessibility, facilities, and attractiveness to 100 respondents, then processed using the SPSS version 20 program. Instrument testing through validity and reliability tests. Testing requirements analysis through normality test, linearity test, and homogeneity test. Hypothesis testing is done through multiple linear regression models, partial t-test, and F simulative test. Then analyze the coefficient of determination (R2) and statistical hypotheses. The results showed that accessibility and facilities had a significant and insignificant effect on visitor satisfaction. While the attractiveness and significant effect on visitor satisfaction.